AB1168-HPR Physical Inacivity in Adults with Rheumatic Diseases. (10th June 2014) - Tonga, E.; Acar, M.; Daskapan, A.
Abstract : Background: Physical inactivity is a frequent complication of rheumatic diseases, and also common in the general population. However, there is surprisingly little research available comparing daily life physical activity between patients with rheumatic diseases and healthy controls.The new studies recommend that healthcare professionals encourage people with rheumatic conditions to participate in regular physical activity to improve aerobic fitness and increase the quality of life. The first step in this issue that determine the level of physical activity in people with rheumatic disease. Objectives: The aim of this study was to evaluate levels of physical activity of patients with rheumatoid arthritis, osteoarthritis and fibromyalgia and to compare the results with healthy subjects and each other. Methods: Our study was carried out on 50 rheumatoid arthritis patients (age: 51, 98±9, 50), 95 osteoarthritis patients (Age: 52, 98±6, 83) and 82 fibromyalgia patients (Age: 53, 62±7, 12) who have been diagnosed in Baskent University Hospital Rheumatology department and 110 healthy subjects (Age: 51, 7±8, 37). The International Physical Activity Questionnaire (IPAQ) was used to determine the level of physical activity. All sub parameters score (walking, moderate intensity PA, vigorous intensity PA, total PA) in IPAQ were calculated. All datas were compared between rheumatic diseases (rheumatoid arthritis, osteoarthritis, fibromyalgia) and healthy controls, and each other. Results: Age, body mass index, disease duration, education levels of patients were similar. There were significant differences in walking and total physical activity scores in IPAQ between the rheumatoid arthritis, osteoarthritis, fibromyalgia patients and the control group (p<0.05). 36.6% of the fibromyalgia group, 28.4% of the osteoarthritis group, 38% of the rheumatoid arthritis group and 22.7% of healthy subjects were found to be inactive. 45.1% of the fibromyalgia group, 42.1% of the osteoarthritis group, 46% of the rheumatoid arthritis group and 36.4% of healthy subjects were found to be insufficiently active. Conclusions: As a result, when compared to healthy people, physical activity levels were significantly decreased in patients with rheumatoid arthritis, osteoarthritis, fibromyalgia. The decrease of physical activity levels were more clear in patients with rheumatoid arthritis than in patients with osteoarthritis and fibromyalgia. In cases of rheumatic diseases, exercise and daily physical activity programs must be included in physiotherapy and rehabilitation treatment approaches. References: Manning V, Hurley M, Scott D, Bearne L. Physıcal Inactıvıty In Adults Wıth Rheumatıc Condıtıons.British Health Professionals Rheumatology. 2011. Abstract. De Groot, IB., Bussmann, JB., Stam, HJ., Verhaar, JA. (2008). Actual everyday physical activity in patients with end-stage hip or knee osteoarthrit is compared with healthy controls. Osteoarthritis Cartilage. 16(4): 436e42. Raftery, G., Bridges, M., Heslop, P., Walker, DJ. (2009). Are fibromyalgia patients as inact ive as they say they are? Clin Rheumatol. 28(6): 711-4. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4551